Imprisoned by the past : Warren McCleskey and the American death penalty - Kirchmeier, Jeffrey L. (New York : Oxford University Press, 2015)
'Imprisoned by the Past' recounts the history of the American death penalty and connects that history to the case of Warren McCleskey. By highlighting the relation between American history and an individual case it provides a unique understanding of the big picture of capital punishment in the context of a compelling human story.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Capital punishment -- United States; McCleskey, Warren -- Trials, litigation, etc; Discrimination in criminal justice administration -- United States